PENGARUH KEMAMPUAN DIGITAL GURU DAN PENERAPAN DEEP LEARNING DALAM PENINGKATAN KUALITAS PEMBELAJARAN DI SEKOLAH DASAR - Nunung Nurbaya; Suryadi; Nugraha Suharto (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze the effect of teachers’ digital competence and the implementation of deep learning on the quality of learning in primary schools. The research employed a quantitative approach using Structural Equation Modeling with Partial Least Squares (SEM-PLS). Respondents consisted of primary school teachers in Sukatani District, Purwakarta Regency selected through purposive sampling. Data were collected using a Likert-scale questionnaire. The results show that teachers’ digital competence has no significant direct effect on learning quality (β = 0,267; t = 1,348; p = 0.178). Teachers’ digital competence significantly affects deep learning implementation (β = 0,731; t = 5,222; p = 0.000). Deep learning significantly influences learning quality (β = 0,685; t = 4,241; p = 0.000). Furthermore, the indirect effect of teachers’ digital competence on learning quality through deep learning is significant (β = 0,501; t = 2,181; p = 0.029). These findings highlight the mediating role of deep learning in enhancing learning quality driven by teachers’ digital competence. Keywords: digital competence, deep learning, learning quality, SEM-PLS